Predictive Role of Attachment Styles and Emotion Regulation on Forgiveness in Married People - Ozlem Tagay; Faika Merve Karadoğan (Psikiyatride Güncel Yaklaşımlar, 2022)
Marriage is one of the important steps that spouses tend to be happy together and raise future generations. However, in the marriage life made with hope, there may be hurt and resentment as well as happy moments. After the negative situations where resentment occurs between spouses, they sometimes decide to get through relationship and sometimes they can choose to forgive each other by resolving their conflicts. For this reason, it is important to research forgiveness in marriage, taking into account the conflicts between spouses. The purpose of this research is investigating the predictive role of attachment styles and emotion regulation skills on forgiveness in married individuals. The study group consisted of 236 individuals, between the ages of 18-65, who were married for at least 1 year. In this study, "Experiences in Close Relationships- Revised", "Marriage Forgiveness Scale-Event" and "Interpersonal Emotion Regulation Questionnaire: Co-Brooding and Co-Reappraisal" scales were used to collect data. According to the results of the research, as the avoidant attachment and brooding scores increase, the benevolence dimension score of the forgiveness scale decreases; as the anxious attachment, avoidant attachment and co-brooding scores increase, the avoidance dimension score of forgiveness increases, that is, the tendency to forgive decreases; while only anxious attachment predicted the retaliation dimension of forgiveness, co-reappraisal did not predict dimensions of the forgiveness scale.